Farfantepenaeus subtilis (Pérez-Farfante, 1967) and F. brasiliensis (Latreille, 1817) (Decapoda, Penaeidae): Ontogenetic comparison using the combined analysis of secondary sexual characters and molecular markers - França, Nielson Felix Caetano; Moraes, Alex Barbosa de; Carvalho-Batista, Abner [UNESP]; Melo, Marília Carla Ramos Barreto de; López-Greco, Laura; Mantelatto, Fernando Luis; Freire, Fúlvio Aurélio de Morais (Elsevier, 2019)
Most identification keys of species of Farfantepenaeus use the shape of secondary sexual characters as a dichotomic character, but this approach focus only on adults. The lack of similar diagnostic tools for juveniles, which are commonly found in sympatry in estuaries, hinders the identification of the species Farfantepenaeus subtilis and Farfantepenaeus brasiliensis. To fill this gap, here we described the morphology of their secondary sexual characters along ontogeny and confirmed the efficiency of these characters using molecular tools. Moreover, based on morphological analyses of the thelycum and petasma we propose an additional morphological maturity stage, and report the occurrence of positive allometry in both sexes. These results may serve as a baseline for future improvements of the management practices of stocks of these shrimps, and future studies on the systematic, reproductive biology and development of penaeid shrimps.
Keywords: Cytochrome oxidase I; Morphological comparison; Ontogeny and Penaeids; Species differentiation